129k views
1 vote
How do you simplify (2x+5)(3x-12)

User Hila
by
5.9k points

2 Answers

1 vote
Simplifying 2x + 5 + -3x = 12 Reorder the terms: 5 + 2x + -3x = 12 Combine like terms: 2x + -3x = -1x 5 + -1x = 12 Solving 5 + -1x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right.
Add '-5' to each side of the equation. 5 + -5 + -1x = 12 + -5
Combine like terms: 5 + -5 = 0 0 + -1x = 12 + -5 -1x = 12 + -5
Combine like terms: 12 + -5 = 7 -1x = 7
Divide each side by '-1'. x = -7

Simplifying x = -7
User Lord Of The Goo
by
5.4k points
2 votes
By rearranging your terms!

1) First, remove the parentheses.
2x+5+3x-12

2) Next rearrange like terms together
2x+3x+5+(-12)

3) Now combine like terms!
2x+3x= 5x
5 +(-12)= -7

4) Final answer: 5x+(-7)

User Ali Ahmed
by
5.8k points